Before I sleep : memoirs of a modern police commissioner - Whitrod, Ray, 1915- (St Lucia, Qld. : University of Queensland Press, 2001)
"In the depths of the Depression, while cycling around the South Australian Riverlands in a vain attempt to find fruitpicking work, a young Ray Whitrod learned of a recruitment scheme for teenage police cadets. He set off for Adelaide and a copper's life. In 1976 Whitrod resigned as police commissioner of Queensland, no longer willing to tolerate the interference of the Bjelke-Petersen government. It was a decision that the Fitzgerald Inquiry would later, gloriously vindicate." "In the years between these events Ray Whitrod rose through the ranks to command not only the Queensland police but the Commonwealth and the Papua New Guinea forces as well. In wartime, he had trained and flown as a navigator with the RAF in Europe and the Middle East. After the war, he helped to found ASIO, operating both in the field and from behind a desk.".
"Retirement was to prove almost more incident-packed than his official career. Ray Whitrod lectured in criminology at the Australian National University, worked with cancer sufferers, visited prisons and, together with his wife Mavis, was the driving force behind the establishment of the Victims of Crime Service." "At once a personal memoir and a rare, insider's view of the police profession in transition, Before I Sleep tells of a life both distinguished and humble."--BOOK JACKET.
Keywords: Whitrod, Ray, -- 1915-; Police -- South Australia -- Biography; Police -- Queensland -- History